Evaluation of storage facilities for groundnut and cowpea in the Zabzugu and Saboba Districts in the Northern Region of Ghana - Abdul-Rahim, Mohammed (2014)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment of the requirements for the award of Master of Philosophy degree in Postharvest Technology.